Implementation of Sharia Financial Products for MSMEs in Medan: Perspectives of Entrepreneurs and Financial Institutions - Yudistira Abdi; Andriana Alnazhira Chandra; Mustafa Kamal Rokan; Imaduddin Sani (Islamiconomic : Jurnal Ekonomi Islam, 2025)
This study examines the role of sharia financial products in supporting MSMEs in Medan, the challenges encountered, and potential solutions for optimization. Using a qualitative case study with 12 informants, data were gathered through in-depth interviews, field observations, and document analysis. The findings show that MSMEs’ understanding and acceptance of sharia financial products remain limited due to low literacy and a preference for conventional finance. Key challenges include complex procedures, restricted access, weak product innovation, and insufficient regulatory support at the local level. To address these barriers, the study proposes strengthening financial literacy education, developing innovative products tailored to micro-enterprises, enhancing digital infrastructure, and encouraging collaboration among government, financial institutions, and business communities. The novelty of this research lies in its dual perspective, integrating insights from both MSME actors and Islamic financial institutions, which is rarely examined in prior studies. This dual lens provides a more holistic understanding of the interaction between demand and supply in sharia finance. The study contributes to the Islamic economics literature by presenting the unique case of Medan, while offering policy implications that emphasize localized literacy strategies, regulatory reforms, and innovation to achieve inclusive and competitive sharia finance aligned with maqasid al-shariah.